1994
DOI: 10.1103/physrevlett.72.1380
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of sonoluminescence to experimental parameters

Abstract: Light-scattering measurements have enabled us to determine that the transition to sonoluminescence is characterized by a bifurcation in the dynamics of a trapped pulsating bubble. These experiments also reveal that in the sonoluminescence (SL) state, changes in bubble radius of only 20% are associated with factors of 200 in the intensity of emitted light. This sensitivity of SL suggests that it originates from the kind of singular behavior that arises from the implosion of a shock wave. Theoretical extrapolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
1
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 12 publications
12
145
1
4
Order By: Relevance
“…The triggering of the collapse of nanobubbles may result from a local electromagnetic perturbation induced by the transition of oxygen into a singlet state [20]. It is known that the temperature and pressure inside a collapsing bubble are sufficient to overcome the energy threshold (E a = 941.4 kJ/mol) of the break of triple bonds in the nitrogen molecule [44].…”
Section: Discussionmentioning
confidence: 99%
“…The triggering of the collapse of nanobubbles may result from a local electromagnetic perturbation induced by the transition of oxygen into a singlet state [20]. It is known that the temperature and pressure inside a collapsing bubble are sufficient to overcome the energy threshold (E a = 941.4 kJ/mol) of the break of triple bonds in the nitrogen molecule [44].…”
Section: Discussionmentioning
confidence: 99%
“…17 The dependence of viscosity, gas solubility, and water vapor pressure on water temperature conspire to allow for larger maximal SBSL light intensities at lower water temperatures. 16,38 Further studies 17,37 elucidated the possibilities for achieving SL in larger bubbles or with more violent collapses ͑''upscaling''͒.…”
Section: B the Merits Of The Bubble Dynamical Approachmentioning
confidence: 99%
“…The spectrum of the emitted light indicates that the surface of the emitting bubble may be hotter than the surface of the sun [4]. It has been proposed [5] that the interior of the bubble may be hot and dense enough to facilitate thermonuclear fusion. In a recent paper Taleyarkhan et al [6] reported the possible observation of d-d fusion events occurring in collapsing bubbles formed by cavitation in deuterated acetone.…”
mentioning
confidence: 99%